Examining the relationship between anxiety and pathological demand avoidance in adults: a mixed methods approach - Johnson, Matt; Saunderson, Helen (Frontiers in Education, 2023)
Pathological demand avoidance (PDA) is characterised by extreme avoidance of everyday demands. A recent study identified anxiety and intolerance of uncertainty (IU) as explanatory frameworks for understanding PDA in children, while anecdotal evidence suggests that anticipatory responses to uncertainty are also influential in the development and maintenance of PDA. Previous studies have relied upon parent-report of child representations of PDA; the lack of adult representation in the literature means that little can currently be said for how demand avoidance behaviours manifest in adulthood. The present study aimed to further an understanding of underlying mechanisms involved in the development and maintenance of PDA by recruiting a non-clinical adult cohort. Experiment 1 utilised a correlational survey design in order to ascertain the extent to which MASQ-D30, IUS-12 and SBI scores could be used to predict EDA-QA scores (N= 163). In experiment 2, a subsample of participants from experiment 1 (n= 13) gave their experiential perspective on anxiety, uncertainty and anticipation. Regression analysis found only MASQ-D30 and IUS-12 scores to significantly predict that of the EDA-QA. Additionally, interpretive phenomenological analysis of participant transcripts revealed four main themes (approach-avoidance behaviour, factors influencing anticipatory bias, vulnerability factors associated with demand avoidance, and development). Taken together, results from experiments 1 and 2 support the notion that anxiety and IU continue to play a role in the maintenance of PDA behaviours in adulthood, while participant descriptions implicate the role of anticipatory responses to uncertainty in the maintenance of demand avoidant behaviours in adults.